Pendampingan Guru dalam Penyusunan Bahan Ajar Kurikulum Merdeka: Pengalaman Madrasah di Banten - Farhurohman, Oman; Sabri, Sabri; Hanafi, Hanafi; Purwanti, Dewi; Nurbayinah, Siti; Aditiya Subagja, Muchamad (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
The problems teachers at MIN 1 Serang face in preparing teaching modules for the Merdeka Curriculum include difficulties in designing and creating the modules and a lack of experience implementing them in the classroom. This activity aimed to assist teachers in overcoming these challenges, particularly in designing and creating teaching modules for the Merdeka Curriculum. The method used was Participatory Action Research (PAR), which involved four stages: preparation and coordination, implementation, mentoring, and program evaluation. The mentoring process began with the preparation and coordination stage, which included identifying needs and planning activities at the school. Subsequently, the implementation phase involved intensive training to understand the Merdeka Curriculum and techniques for creating teaching modules, followed by in-depth mentoring to prepare Merdeka Lesson Plans. During the mentoring process, participants were encouraged to think critically and comprehensively when designing teaching materials. The results of this activity showed positive changes, where participants could understand the Merdeka Curriculum materials and successfully create teaching modules per the curriculum's standards. The evaluation at the end of the activity demonstrated success in achieving the mentoring objectives. Keywords: Teacher assistance, Implementation of Merdeka Curriculum, Teaching modules Abstrak: Problematika yang dihadapi oleh guru-guru di MIN 1 Serang dalam penyusunan modul ajar Kurikulum Merdeka meliputi kesulitan dalam menyusun dan membuat modul ajar, serta kurangnya pengalaman dalam mengimplementasikannya di kelas. Tujuan dari pelaksanaan kegiatan ini adalah untuk mendampingi guru dalam mengatasi permasalahan tersebut, khususnya dalam menyusun dan membuat modul ajar Kurikulum Merdeka. Metode yang digunakan adalah Participatory Action Research (PAR), yang melibatkan empat tahapan: persiapan dan koordinasi, pelaksanaan, pendampingan, serta evaluasi program. Proses pendampingan dimulai dengan tahap persiapan dan koordinasi, yang mencakup identifikasi kebutuhan dan perencanaan di madrasah. Selanjutnya, pelaksanaan pendampingan dilakukan melalui pelatihan intensif untuk memahami Kurikulum Merdeka dan teknik penyusunan modul ajar, diikuti dengan pendampingan intensif dalam penyusunan RPP Merdeka. Selama proses pendampingan, peserta diajak untuk berpikir kritis dan menyeluruh dalam merancang materi modul ajar. Hasil dari kegiatan ini menunjukkan adanya perubahan positif, di mana peserta mampu memahami materi Kurikulum Merdeka dan berhasil membuat modul ajar sesuai dengan ketentuan kurikulum tersebut. Evaluasi di akhir kegiatan menunjukkan keberhasilan dalam pencapaian target pendampingan. Kata kunci: Pendampingan guru, Implementasi Kurikulum Merdeka, Modul ajar